Creative Learning Ecosystems in Early Childhood Education: Integrating Arts, Technology, and Nature Exploration - Meilani, Muna; Hanafiah, Nur Arifah (Journal of Gemilang, 2026)
Creative learning ecosystems in early childhood education have gained increasing attention as an approach to support children’s holistic development through diverse and meaningful learning experiences. Integrating arts, technology, and nature exploration in early childhood learning environments can stimulate creativity, critical thinking, and socio-emotional development. However, many early childhood education institutions still implement these elements separately, which limits their potential impact on children’s development. Therefore, this study aims to analyze how the integration of arts, technology, and nature exploration contributes to the development of creative learning ecosystems in early childhood education and to formulate an integrative conceptual framework that manages these elements as a unified learning ecosystem. This study employs a qualitative approach using a systematic literature review method. Data were collected from peer-reviewed journal articles published between 2021 and 2025 related to creative learning environments, STEAM education, arts-based learning, and nature-based learning in early childhood education contexts. The data were analyzed through thematic and conceptual synthesis to identify patterns, relationships, and conceptual models related to creative learning ecosystems. The findings indicate that play-based learning, artistic expression, technological exploration, and nature-based learning collectively support children’s cognitive, social, emotional, and physical development. The study concludes that an integrative framework combining arts, technology, and nature exploration within holistic learning environments is essential for developing sustainable creative learning ecosystems in early childhood education